Some Characteristics of the Annual Precipitation Cycle in Central America and their Relationships with its Surrounding Tropical Oceans - Alfaro Martínez, Eric J. (2002)
Artículo científico -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2002